USE OF INFORMATION TECHNOLOGIES IN THE LESSONS OF INDUSTRIAL TRAINING (Innovative professional education, 2025)
The article examines the use of information technology (IT) in industrial training lessons. The role of digital tools in the training of future specialists, the impact of modern technologies on the effectiveness of the educational process and the formation of key competencies of students are analyzed. The main advantages of integrating IT into the educational process are revealed, in particular: the use of multimedia tools (Microsoft PowerPoint, Google Slides, Canva, Keynote, Prezi).
Keywords: Information technology, industrial training, digital education, vocational education, multimedia presentation